Pharmacological evaluation of enantiomerically separated positive allosteric modulators of cannabinoid 1 receptor, GAT591 and GAT593 - Brandt, Asher L.; Garai, Sumanta; Zagzoog, Ayat; Hurst, Dow P.; Stevenson, Lesley A.; Pertwee, Roger G.; Imler, Gregory H.; Reggio, Patricia H.; Thakur, Ganesh A.; Laprairie, Robert B. (Frontiers in Pharmacology, 2022)
Positive allosteric modulation of the type 1 cannabinoid receptor (CB1R) has substantial potential to treat both neurological and immune disorders. To date, a few studies have evaluated the structure-activity relationship (SAR) for CB1R positive allosteric modulators (PAMs). In this study, we separated the enantiomers of the previously characterized two potent CB1R ago-PAMs GAT591 and GAT593 to determine their biochemical activity at CB1R. Separating the enantiomers showed that the R-enantiomers (GAT1665 and GAT1667) displayed mixed allosteric agonist-PAM activity at CB1R while the S-enantiomers (GAT1664 and GAT1666) showed moderate activity. Furthermore, we observed that the R and S-enantiomers had distinct binding sites on CB1R, which led to their distinct behavior both in vitro and in vivo. The R-enantiomers (GAT1665 and GAT1667) produced ago-PAM effects in vitro, and PAM effects in the in vivo behavioral triad, indicating that the in vivo activity of these ligands may occur via PAM rather than agonist-based mechanisms. Overall, this study provides mechanistic insight into enantiospecific interaction of 2-phenylindole class of CB1R allosteric modulators, which have shown therapeutic potential in the treatment of pain, epilepsy, glaucoma, and Huntington's disease.